International Aspects of Mental Health Work with Refugees and Future Directions A European Perspective - Hauff, Edvard; Minnesota Univ., Minneapolis. Refugees Assistance Program - Mental Health Technical Assistance Center ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
This paper describes past and present European efforts to address the mental health needs of refugees. It begins with a brief historical survey of mental health services for refugees after the Second World War and delineates the policy recommendations from the 1948 International Congress on Mental Health. The next section describes current programs in Belgium, France, the Netherlands, Norway, Sweden, Denmark, and Germany. Following this, special programs in Copenhagen, Stockholm, London, and Oxford for refugees who have been exposed to torture are described. Recent international conferences in Europe involving representatives of the various medical and psychosocial centers for refugees in Europe are next described, along with documentation centers and networks and international journals on refugee issues based in Europe. Future directions are outlined for mental health work with refugees: briefly discussed are research and training needs, international networking, new journals, and planned conferences. The paper concludes with a call for greater cooperation between refugee mental health programs in Europe and North America with those in Third World countries. (TE)
Availability: Refugee Assistance Program--Mental Health Technical Assistance Center, University of Minnesota, Box 85, Mayo, Minneapolis, MN 55455.
Sponsoring Agency: National Inst. of Mental Health (DHHS), Rockville, MD.
Contract Number: NIMH-278-85-0024-CH.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Conferences; European History; Foreign Countries; International Programs; Mental Health Programs; Program Descriptions; Psychiatric Services; Refugees; Rehabilitation; Research Needs; Victims of Crime; Refugee Mental Health; Refugee Assistance -- Torture Victims; Opinion Papers; Reports, General